Proceedings of the the 1st ACM Workshop on Continuous Archival and Retrieval of Personal Experiences 2004
DOI: 10.1145/1026653.1026662
|View full text |Cite
|
Sign up to set email alerts
|

Personal chronicling tools for enhancing information archival and collaboration in enterprises

Abstract: One of the greatest challenges in enterprises today is the lack of dynamic and ongoing information about individuals' activities, interests, and expertise. Availability of such "personal chronicles" can provide rich benefits at both an individual and enterprise level. For example, personal chronicles can help individuals to far more effectively retrieve and review their activities and interactions, while at an enterprise level they can be data-mined to identify groups of common and complementary interests and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A lot of literature here centres upon how personal data may be used to inform things such as advertising [35][58], service development [15][30] [74], product development, or direct marketing [57]. There is also some interest in how it may be used to support the identification of potential recipients of advice or instruction [42]. On the back of this come debates about the ways in which use may actual constitute misuse.…”
Section: The Use Of Personal Data and Associated Threatsmentioning
confidence: 99%
“…A lot of literature here centres upon how personal data may be used to inform things such as advertising [35][58], service development [15][30] [74], product development, or direct marketing [57]. There is also some interest in how it may be used to support the identification of potential recipients of advice or instruction [42]. On the back of this come debates about the ways in which use may actual constitute misuse.…”
Section: The Use Of Personal Data and Associated Threatsmentioning
confidence: 99%
“…For example, Henderson has looked at how people organize their desktops [17] and Jones et al have reported on the extensive use of desktop folders [18]. Other researchers have studied in detail the use, archiving and/or storage of emails [4,5,10,23], of documents [8], of time management tools [7], of To Do lists [3] and personal information management software [3,6,19,20].…”
Section: Archiving In Hcimentioning
confidence: 99%
“…One of the approaches is to augment the standard browsing or searching facilities that were discussed in section 3.3.1. For example, Kim et al [2004] suggested that search facilities for personal information could be improved by using document and query expansion with the thesaurus facilities of Wordnet. This was an attempt to remove the need for users to remember exact terms that appear in documents when they construct re-finding queries.…”
Section: Tools For Re-findingmentioning
confidence: 99%